The protein disulfide isomerase 1 of Phytophthora parasitica (PpPDI1) is associated with the haustoria-like structures and contributes to plant infection - Meng, Yuling; Zhang, Qiang; Zhang, Meixiang; Gu, Biao; Huang, Guiyan; Wang, Qinhu; Shan, Weixing (Frontiers in Plant Science, 2015)
Protein disulfide isomerase (PDI) is a ubiquitous and multifunction enzyme belonging to the thioredoxin (TRX) superfamily, which can reduce, oxidize, and catalyze dithiol–disulfide exchange reactions. Other than performing housekeeping functions in helping to maintain proteins in a more stable conformation, there is some evidence to indicate that PDI is involved in pathogen infection processes. In a high-throughput screening for necrosis-inducing factors by Agrobacterium tumefaciens-mediated transient expression assay, a typical PDI gene from Phytophthora parasitica (PpPDI1) was identified and confirmed to induce strong cell death in Nicotiana benthamiana leaves. PpPDI1 is conserved in eukaryotes but predicted to be a secreted protein. Deletion mutant analyses showed that the first CGHC motif in the active domain of PpPDI1 is essential for inducing cell death. Using P. parasitica transformation method, the silencing efficiency was found to be very low, suggesting that PpPDI1 is essential for the pathogen. Translational fusion to the enhanced green fluorescent protein (EGFP) in stable P. parasitica transformants showed that PpPDI1 is associated with haustoria-like structures during pathogen infection. Furthermore, the PpPDI1-EGFP-expressing transformants increase the number of haustoria-like structures and exhibit enhanced virulence to N. benthamiana. These results indicate that PpPDI1 might be a virulence factor of P. parasitica and contributes to plant infection.